Bilingual lexical decision: Effect of language proficiency and primes - Prema K S; Prarthana S; Abhishek B P (Journal of All India Institute of Speech and Hearing, 2013)
Bilinguals may have varying degrees of proficiency over their two languages. Assessment of bilingual proficiency by employing tools developed for non-Indian population is not suitable to the bilingual population in India. Tools developed indigenously for quick and objective assessment of language proficiency is warranted. Therefore, the present study assessed performance of 30 Kannada-English bilinguals in primed lexical decision task (LDT) with three different prime types- translation equivalent, semantically related and semantically unrelated primes along with self-rating questionnaire, LEAP-Q. Good correlation of scores on questionnaires and reaction time for LDT suggest that primed LDT serves as a test for bilingual proficiency. Among the prime types, the translation equivalent prime indicated proficiency better than the semantically related and semantically unrelated stimuli. Results of the study suggest that primed lexical decision task can be used as a tool for assessing proficiency based on the performance of individuals as against only competence assessed through questionnaires.